POLYSEMY, HOMONYMY AND OTHER SOURCES OF AMBIGUITY IN THE LANGUAGE OF CHINESE CONTRACTS - GRZYBEK, Joanna (Comparative Legilinguistics, 2009)
Th is paper discusses the main sources of ambiguity in Chinese-Polish translation of the contract legal language. Legal Chinese is very often the same as ordinary formal Chinese and that fact causes ambiguity in Chinese contracts. Th e author focuses on polysemy and homonymy which make the interpretation of legal language diffi cult and ambiguous. The meaning of Chinese characters depends on the textual context. However, when an interpreter does not know the background information of translated legal texts, it is very diffi cult to achieve a high quality legal translation. The abundance of homophones in Chinese language also poses a problem, especially in the case of contracts concluded in words, not in writing. The paper further presents different grammatical functions of Chinese terms encountered in contracts without a morphological change. Such linguistic features of Chinese language as: the absence of distinction between singular and plural nouns, lack of infl ection, no grammatical categories of tense and aspect cause ambiguity and vagueness in interpreting the Chinese agreements. Moreover, the understanding of such texts is sometimes incorrect due to omissions and elliptical sentences. The author also shows the diff erences in the meaning of terms, which apparently signify the same entities and concepts in Polish and Chinese legal languages but in fact diff er signifi cantly.